Single Molecule Magnet Features in the Butterfly [CoIII2LnIII2] Pivalate Family with Alcohol-Amine Ligands - Funes, Alejandro; Perfetti, Mauro; Kern, Michal; Russegger, Nadine; Carrella, Luca; Rentschler, Eva; Van Slageren, Joris; Albores, Pablo (European Journal of Inorganic Chemistry, 2021)
We are reporting the synthesis and structural characterization of a new family of butterfly complexes with formula [Co2IIILn2III−(μ3−(OR))2] where −OR is an alcohol-amine type ligand, in this case N-methyldiethanolamine (H2mdea) with Ln=Tb, Dy, Ho, Er and Yb. This new family adds to the previously reported one, where the alcohol-amine ligand is triethanolamine (H3tea), and allows a one-to-one comparison between them. From a combined experimental study, that included DC and AC magnetometry as well as HF-EPR measurements, and a theoretical approach based on Broken-Symmetry DFT and CASSCF-SA-SOC ab-initio computations, we discuss the single molecule magnet (SMM) performance in these complexes. We focus in a few key structural parameters that correlate with the magnetization relaxation behaviour observed along the different explored lanthanide ions.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Ab-initio; HF-EPR; Lanthanide; Magnetization relaxation; SMM